2018
DOI: 10.1021/acs.chemrev.7b00551
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Polycyclic Polyprenylated Acylphloroglucinols

Abstract: Polycyclic polyprenylated acylphloroglucinols (PPAPs) are a class of hybrid natural products sharing the mevalonate/methylerythritol phosphate and polyketide biosynthetic pathways and showing considerable structure and bioactivity diversity. This review discusses the progress of research into the chemistry and biological activity of 421 natural PPAPs in the past 11 years as well as in-depth studies of biological activities and total synthesis of some PPAPs isolated before 2006. We created an online database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
281
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(282 citation statements)
references
References 408 publications
0
281
0
1
Order By: Relevance
“…By contrast, several studies have indicated that TRPC6 channels could also be store-operated (Yu et al, 2003;El Boustany et al, 2008). Hyperforin has been shown to specifically activate TRPC6 channels, which is mainly responsible for the antidepressant effect of St. John's wort (Yang et al, 2018). There is also a close relation between TRPC6 and reactive oxygen species.…”
Section: Structure and Characteristics Of Trpc6mentioning
confidence: 99%
“…By contrast, several studies have indicated that TRPC6 channels could also be store-operated (Yu et al, 2003;El Boustany et al, 2008). Hyperforin has been shown to specifically activate TRPC6 channels, which is mainly responsible for the antidepressant effect of St. John's wort (Yang et al, 2018). There is also a close relation between TRPC6 and reactive oxygen species.…”
Section: Structure and Characteristics Of Trpc6mentioning
confidence: 99%
“…[11] Several reviews and book chapters covered the extensive chemistry and biological activities of garcinol and isogarcinol over the last decade. [4,6,7,10,11] The present review highlights the most recent proceedings in this field.…”
Section: Introductionmentioning
confidence: 98%
“…Their modes of action are diverse and include the inhibition of NF‐ κ B and STAT as well as of histone acetyl transferases (HATs) . Several reviews and book chapters covered the extensive chemistry and biological activities of garcinol and isogarcinol over the last decade . The present review highlights the most recent proceedings in this field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations